Using a poetic corpus for phonological studies in archaic portuguese: the case of elision - Favaro, Gisela Sequini (2022)
This article aims to show the importance of choosing a poetic corpus (in this case, religious songs in praise of the Virgin Mary, called Cantigas de Santa Maria - CSM) in order to study phonological processes in Ancient Portuguese (PA), specifically referring to prosodic phenomena, such as elision. The intention is to elucidate, through writing, questions related to the sounds of language, in both levels, segmental and suprasegmental. As elision is a phonological process of vowel deletion in vocabular junction, mapping its occurrences is the first step to investigate the vowels involved and the conditioning factors, such as syllable structure and stress incidence. Considering poetic texts is crucial, specially in the case of elision, to confirm (or not) the vowel deletion.